2014
DOI: 10.1093/ejcts/ezu175
|View full text |Cite
|
Sign up to set email alerts
|

Mitral valve repair with loop technique via median sternotomy in 180 patients

Abstract: The loop technique via median sternotomy to treat posterior, anterior and, especially, bileaflet prolapse provided satisfactory mid-term outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 21 publications
1
33
0
2
Order By: Relevance
“…In 2016, after carefully analyzing results in the literature, we observed that in more than 2300 patients, the length of the posterior and anterior loops ranged from 13.7 to 18 mm and from 21.1 to 26 mm, respectively. 14, 15 That is why we decided to use the standardized approach with implantation of 15 mm and 25 mm loops for posterior and anterior prolapses, respectively. 3 In our experience, we did not adapt the length of the loops to any particular anatomical situation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, after carefully analyzing results in the literature, we observed that in more than 2300 patients, the length of the posterior and anterior loops ranged from 13.7 to 18 mm and from 21.1 to 26 mm, respectively. 14, 15 That is why we decided to use the standardized approach with implantation of 15 mm and 25 mm loops for posterior and anterior prolapses, respectively. 3 In our experience, we did not adapt the length of the loops to any particular anatomical situation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, anchoring of the loop on the prolapsed mitral segment is also important. Like Shibata and colleagues, 15 we used polypropylene sutures because we were familiar with these sutures in classic mitral valve repairs. Recently, and after the reoperation of one of our patients in whom a ruptured polypropylene suture was found, we have changed our strategy and use a Gore-Tex suture to anchor the mitral prolapsed segment to the loop.…”
Section: Discussionmentioning
confidence: 99%
“…Sau phẫu thuật chức năng thất trái hồi phục tốt (Biểu đồ 2): tim nhỏ lại, giảm thể tích thất trái, giảm kích thước buồng thất trái; sự hồi phục thất trái cả thì tâm thu và tâm trương về bình thường [2], [7]. Ngoài ra, kích thước Nhĩ trái cũng cải thiện: trước phẫu thuật, đường kính nhĩ trái trung bình là 50.7mm, được cải thiện tốt sau mổ 1 tháng với kích thước trung bình là 40.72mm, và tiếp tục cải thiện về kích thước trung bình là 40.67mm.…”
Section: Sự Thay đổI Về Kích Thước Buồng Tim Sau Phẫu Thuậtunclassified
“…Nghiên cứu của tác giả Toshiko Shibata sửa van hai lá dùng dây chằng nhân tạo đa vòng qua đường mở giữa xương ức trên 180 bệnh nhân có kết quả: số vòng lặp trung bình sử dụng cho lá trước là 2 vòng lặp, lá sau là 2 vòng lặp và cả hai lá trước sau là 3 vòng lặp; Chiều dài dây chằng trung bình ở lá trước là 18mm, lá sau là 17mm, cả hai lá là 18mm [10].…”
Section: Dây Chằng Nhân Tạo Mang Tính Linh Hoạtunclassified